Anthocyanin profiles and color properties of red wines made from Vitis davidii and Vitis vinifera grapes - Yanlun Ju; La Yang; Xiaofeng Yue; Yunkui Li; Rui He; Shenglin Deng; Xin Yang; Yulin Fang (Food Science and Human Wellness)
Spine grape (Vitis davidii Foex.) is an important wild grape species native to China. Fifteen red spine grape clones and three red Vitis vinifera grape varieties were used to evaluate the differences in the anthocyanin profiles and color properties of wines made from V. davidii and V. vinifera grapes. Among spine wines, ‘Junzi #2’ wine had the highest total phenolic and total anthocyanin, ‘Xiangzhenzhu’ wine had the highest total flavonoids, and ‘Junzi #1’ wine had the highest total tannin. The anthocyanin compositions of all of the spine wines were dominated by Mv-3,5-diglucoside. The total individual anthocyanin contents in spine wines, except ‘Gaoshan #5’, ‘Junzi #5055’, ‘Junzi #5061’, and ‘Junzi #5044’, were significantly higher than in V. vinifera wines. Most of the spine wines had a stronger red intensity and a brighter chroma with a bluer hue than V. vinifera wines. Correlation analysis revealed that the color properties were closely related to the anthocyanin composition. These results suggest that wines made from spine grapes may be useful for the wine industry for their color properties and high individual anthocyanin contents.